Les transgressions poétiques d’un auteur swahiliphone de Lubumbashi : Patrick Mudekereza - Flavia Aiello; Roberto Gaudioso (Continents manuscrits)
This paper reports on field research carried out as part of a Project of National Interest (PRIN) entitled “Mobility - Stabilisation. Congolese representations and social dynamics, in Congo and in the global space”, funded for the period 2017-2020 by the Italian Ministry of Education, University and Research. Flavia Aiello and Roberto Gaudioso present unpublished texts by Patrick Mudekereza whom they met in Lubumbashi in 2018. Mudekereza never published his poems in poetry collections, considering his writing essentially as a practice associated with his work dedicated to art. Engaged in several forms of writing, both creative and discursive (the latter in French or English), the artist from Lubumbashi seems to have a very particular and intimate relationship with poetry, which he practises intermittently and of which he does not keep track systematically. In this article we will analyse six texts, three of which (Funga macho liya, Pima tuyambe and Langues) were composed during the work of the writers’ collective Libr’Écrire born in Lubumbashi in 2007; two are undated (Buzuri tele and Mu pori ya binvuri [In the Wood of Shadows]), and one (Mankamanshi>Mboleo [Snot>Fertilising]) is dated 13 February 2018. Three of these poetic compositions are bi/multilingual, in French, Swahili and Lingala (Funga macho liya, Langues, Mankamanshi>Mboleo), the others are written in Swahili.